2019
DOI: 10.1155/2019/1341963
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Bariatric Surgery versus Medication Therapy for Obese Patients with Type 2 Diabetes in China: A Markov Analysis

Abstract: Aims/Introduction. The present study estimated the cost-effectiveness of bariatric surgery versus medication therapy for the management of recently diagnosed type 2 diabetes mellitus (T2DM) in obese patients from a Chinese health insurance payer perspective. Materials and Methods. A Markov model was established to compare the 40-year time costs and quality-adjusted life-years (QALYs) between bariatric surgery and medication therapy. The health-care costs in the bariatric surgery group, proportion of patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…Thirty original articles from 33 publications fulfilled the inclusion criteria. Of these, 16 reported on the cost-effectiveness of metabolic surgery specifically in a T2D population [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], including two empirical studybased economic evaluations [34,40]. Seventeen publications reported on the cost-effectiveness of metabolic surgery in a population with obesity in which a subgroup of the population had T2D [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty original articles from 33 publications fulfilled the inclusion criteria. Of these, 16 reported on the cost-effectiveness of metabolic surgery specifically in a T2D population [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], including two empirical studybased economic evaluations [34,40]. Seventeen publications reported on the cost-effectiveness of metabolic surgery in a population with obesity in which a subgroup of the population had T2D [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
“…Fifteen studies were conducted in European countries [27, 28, 36-38, 43-47, 50, 52, 55, 58, 59], four in the USA [31,32,35,56], three in South America [29,30,49], four in Asia [39][40][41][42], three in Australia [33,34,53], and one in Canada [54].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…RYGB is therefore cost-effective for Chinese patients with T2DM and obesity at 4 years after surgery ( Tu et al, 2019 ). Two other studies also support that, compared with drug treatment of patients with obesity and T2DM, metabolic surgery can bring long-term economic savings ( Tang et al, 2016 ; Wan et al, 2019 ), with more savings from SG ( Tang et al, 2016 ). Wu et al (2021) found that metabolic surgery in patients with obesity and T2DM is expensive, but leads to an improved comorbidity profile, and reduced length of hospitalization.…”
Section: Health Economicsmentioning
confidence: 89%
“…A careful search on Google Scholar of articles on pharmacoeconomic analysis on obesity in China (search keywords: pharmacoeconomic AND obesity AND China) published during 2010-2020 yielded 4,250 hits, but only five studies were identified by two of the co-authors as relevant, with obesity as the primary condition studied and China as the study setting [6,[39][40][41][42].…”
Section: Scoping Reviewmentioning
confidence: 99%
“…health insurance payer and increases in health benefits (2.51 QALY) in a 40-year time horizon, compared to medication therapy[41].…”
mentioning
confidence: 99%